2015
DOI: 10.1001/jamasurg.2014.2346
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Early Readmission After Pancreatectomy to Index and Nonindex Institutions

Abstract: Importance Readmission after pancreatectomy is common, but there is a paucity of data comparing patterns of readmission to index and non-index hospitals. Objective To evaluate the rate of readmission to index and non-index institutions following pancreatectomy at a tertiary high-volume institution, and to identify patient-level factors predictive of those readmissions Design, Setting, Participants Retrospective analysis of a prospectively-collected institutional database linked to statewide data of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
54
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 37 publications
4
54
0
Order By: Relevance
“…18 Despite the ponderous evidence from medical research that associates provider continuity with better patient outcomes and provider fragmentation with lower quality of care and higher costs, 19–22 this hypothesis has not been sufficiently tested in postoperative settings. In the case of major cancer surgery, readmissions are known to be strongly driven by surgical complications, 2,46,10,17,23,24 making provider and information continuity particularly relevant in such scenarios. However, the relationship between location and outcomes of readmission remains largely unexplored among cancer patients, with the exception of gastrectomy and radical cystectomy.…”
mentioning
confidence: 99%
“…18 Despite the ponderous evidence from medical research that associates provider continuity with better patient outcomes and provider fragmentation with lower quality of care and higher costs, 19–22 this hypothesis has not been sufficiently tested in postoperative settings. In the case of major cancer surgery, readmissions are known to be strongly driven by surgical complications, 2,46,10,17,23,24 making provider and information continuity particularly relevant in such scenarios. However, the relationship between location and outcomes of readmission remains largely unexplored among cancer patients, with the exception of gastrectomy and radical cystectomy.…”
mentioning
confidence: 99%
“…Patients who died during their initial hospitalization or within 30 days of surgery (ie, perioperative deaths; n = 13) and those who underwent planned readmission (ie, to rehabilitation institutions; n = 15) were excluded from subsequent analysis 5,9,10 to allow specifically for the study of long-term outcomes. Given the low incidence of minimally invasive pancreatectomy at our institution during the study period, we also excluded subjects who underwent laparoscopic and/or robotic surgery to reduce the potential for confounding.…”
Section: Methodsmentioning
confidence: 99%
“…Additional details regarding the data and methodology used herein have been published previously. 5 This study was approved by the Institutional Review Board at the Johns Hopkins Medical Institutions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study demonstrated that 21.6% of readmissions occurred at regional hospitals and, when accounted for, the observed frequency of readmission increased from 16.9% to 21.5%. 38 Therefore, it is uncertain if all readmissions are captured in this study.…”
Section: Limitationsmentioning
confidence: 99%